Critical Analysis of Pre-Hospital Emergency Care: Paramedics in Action - Al-Yami, Ali Hokash Muhammad; AL Mansour, Hussain Hady Ali; Almalki, Talal Abdulhadi G; Majrashi, Saud Mohammed; Alshehri, Khalid Muaddi Fadhel; Ibnrubayq, Fahad Jazi; Alshammari, Fahad Faleh Eid; Almurdif, Abdulrahman Hamad; Almalki, Muhannad Safar; Alotaibi, Khalid Jazaa Safir (Journal of Ecohumanism, 2024)
Paramedics function within the prehospital context of emergency care because the goal is to get the patient to certain levels of care before being taken to a health facility. Some of their roles include attending to victims in emergency circumstances to make them clinically stable, applying some clinical procedures, and engaging the rest of the health facilities. This paper has reviewed and critiqued the development and functionality of paramedic practices, the problems of operating as a paramedic, and the technological features of today's prehospital care. Proposing that significant enhancements in paramedics' training and inter-professional collaboration are needed, the study's findings portray the contemporary role of paramedics as a crucial segment of healthcare systems and ascribe major responsibilities for enhancing the quality of primary prehospital care.